FIGURATIVE COMPONENT OF THE “MISTOL” CONCEPT IN ARGENTINE FOLKLORE - Lomakina , Irina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
The concept of mistol in Argentine folklore affects the way in which the surrounding world is perceived and also facilitates interaction with this surrounding world. The article clarifies the role of the figurative component of the concept of mistol in the formation of the linguistic picture of the world of Argentines through folklore, studies the interpretations through which this influence takes place, investigates how language and the concept of mistol interact and are interconnected. In the cognitive space of every country there are plants which are symbols. They symbolize beauty, serve as talismans in times of trouble, protect and give health, strength and inspiration, comfort during being in other lands. The mistol concept occupies a prominent place in the Argentine cognitive-linguistic picture of the world, because it is a universal national and spiritual cognitive unit. The main cognitive images in the structure of the mistol concept are “love” and “love for the homeland”. The image of “love” in Argentine folklore is closely connected with the smell of the flowers of this tree and the sweet taste of its fruits. The image of the concept covers a wide information field: “happiness”, “sweet love”, “sweet girl”, “sweet lips of the beloved”. Such a deep conceptualization of mistol on the Argentine folklore ground is indicated by numerous comparisons of this plant with a beloved girl: with her lips, eyes, voice. So the concept of mistol has its anthropomorphic features. The concept of mistol has its stable symbolic part: associatively with a person we talk about beauty, kindness and youth. Also, the information field of mistol embodies the meaning of “my home”, “my area where these trees grow”. Often the concept mistol replaces the name of a locality in northern Argentina, metaphorically pointing to it. This tree, growing near the parental house, is firmly connected with childhood memories. Therefore, mistol evokes cognitive images of “protection”, “amulet”, “hope”. In the numerous folklore examples this tree is mentioned as a sign of this land and expresses adoring of homeland. The perception of “meeting under a tree”, “dancing under a tree”, “resting under a tree” and “enjoying the shade” coincides with the worldview of many other languages. In this meaning, mistol evokes images of happiness, joy, satisfaction, inner warmth, and a sweet life. _____________ References: • Dzherіh, O. S. (2018). “Koncept” u suchasnіj kognіtivnіj lіngvіsticі ta lіngvokul’turologії: ponjattja ta struktura. Typologіja movnih znachen’ u dіahronіchnomu ta zіstavnomu aspektah, 35–36, 61–69. • Prihod’ko, A. M. (2008). Koncepti і konceptosistemi v kognіtivno-diskursivnіj paradigmі lіngvіstiki. Zaporіzhzhja: Prem’єr. • Arboles del Chaco. (n.d.). Rhamnaceae. Retrieved from https://arbolesdelchaco. blogspot.com/search/label/Rhamnaceae • La Cuerda. (n.d.). Buscar acordes de “algarrobo”. Retrieved from https://acordes. lacuerda.net/busca.php?exp=algarrobo&canc=0&ord=0&ini=0 • Cancioneros.com. (n.d.). Buscar letras de “algarrobo”. Retrieved from https://www.cancioneros.com/letras/buscar.php?CT=algarrobo&x=11&y=16 • Folklore y Tradiciones. (n.d.). Cancionero Popular Rioplatense, Tomo I. Retrieved from https://www.folkloretradiciones.com.ar/literatura/Cancionero%20Popular%20Rioplatense%20%20Tomo%20I.pdf